LINGKUNGAN MEMENGARUHI KECEMASAN MAHASISWI TERHADAP DISMENORE DI AKPER HERMINA MANGGALA HUSADA - Ria Anugrahwati; Junita Silitonga (Akademi Keperawatan Hermina Manggala Husada, 2021)
Anxiety is tension, insecurity and worry that arises because it is felt that something unpleasant is happening but whose source is largely unknown and comes from within. Classification of anxiety is divided into several levels, ranging from mild to moderate. Dysmenorrhea is pain that occurs before, during and after menstruation. This study aims to look at the factors that influence the level of anxiety in dealing with dysmenorrhea . This study used a cross-sectional survey study design on 77 female respondents. The results showed that there was a significant relationship between psychological, environmental, sex education, and knowledge factors with female students' anxiety about dysmenorrhea. The unfavorable environment of female students affects female students' anxiety about dysmenorrhea. Recommendations from this study are expected to provide counseling through adolescent clinic facilities to minimize their anxiety about dysmenorrhea, and provide knowledge about menstrual problems, as well as how to overcome anxiety when experiencing dysmenorrhea.